Wolcott-Rallison Syndrome - A Juneja; A Sultan; S Bhatnagar (Wolters Kluwer Medknow Publications, 2012)
Multiple epiphyseal dysplasia with early-onset diabetes mellitus (also known as Wolcott-Rallison syndrome) is a rare autosomal recessive disorder that manifests itself in early infancy with symptoms of diabetes mellitus. Short stature and walking difficulties become evident in the 2 nd year of life when the child starts to walk. These skeletal changes are progressive with age. There is usually a short trunk, excessive lordosis, a short and broad chest, and genu valgum. This report presents a case of Wolcott-Rallison syndrome in a 10 year old child.